Strategi Pengembangan Kemampuan Dan Kreativitas Kewirausahaan Pada Era Digitalisasi - Mesak Iek; Halomoan Hutajulu; Luis Z. Maray; Anselmus Pluto Iek; Julio Yusua Iek (Cenderabakti: Jurnal Pengabdian Kepada Masyarakat, 2023)
The creativity of Sunday school teachers is an absolute necessity in developing the spiritual abilities and skills of Sunday school children. This can take place well, if training and capacity building for Sunday school teachers are carried out regularly, both by the church and in collaboration with related stakeholders. The purpose of the service is to try to improve the ability and entrepreneurial creativity of Sunday school teachers so that when teaching, Sunday school teachers are good at creating an atmosphere that attracts the attention and enthusiasm of Sunday school children to participate in worship (Bible stories) through active, innovative, creative learning methods, effective and fun and convey about entrepreneurship for Sunday school children to members of the GSJA Logos Kotaraja congregation. The method of implementing the training is lectures in the form of delivering material and practice accompanied by the use of teaching aids to Sunday school teachers and members of the GSJA Logos Kotaraja Church. The results of the training showed that there was an increase in the ability of the training participants and there was also an increase in the knowledge of the training members about how to teach creative and innovative Sunday school children, understanding of entrepreneurship for Sunday school children to church members. The results of observations during the training also went well and smoothly and all participants were actively involved in participating in each training session.